Flagellin Immunization against Urinary Tract Infection Caused by p. Mirabilis - Astabraq A. Al-Sodanii (Journal of Global Pharma Technology, 2016)
Objective Proteus mirabilis is dimorphic a (gram negative bacteria that alternates between a rod –shaped swimmer stage and multinucleate, highly elongated swarming stage. Methods  Urine Samples collected from three hospitals in Baghdad city from adult and child patients Suffering from urinary tract infections for 6 months .The samples get reached 1152 distributed among the patients old between few days to 80 years most patients living in hospital with urinary tract catheter , 56 samples of Proteus mirabilis were identified after isolation and diagnosis of bacterial species in different methods because there different complications in UTIs Patients specially Stone formation ,  catheter obstruction , and renal damage. Results these bacteria were diagnosis in api 20 E and vitek2 system and one isolate of Proteus mirabilis was selected for the study according to distance movement by measurement (swarming motility). Flagellin which is the flagella protein was extracted and predicated, followed by SDS-polyacrylamide gel electrophoresis for protein molecular weight estimation and  concentration of protein counted by Bradford method ,then immunization protocol were tested in Albino rabbits in different concentrations 10,20,40 microgram from flagella protein then immunoglobulin antibody IgG ,IgM in serum were tested by single radial immunoglobulin diffusion plate , positive results  showed raised the concentrations of these antibodies with high significant differences .Immunized  females rabbits was tested to ascending urinary tract infection challenge by inoculation 145Ã—107">  cfu from P.mirabilis and tested in 1 , 3 , 7 , 14 days , any  females rabbits didn’t show urinary tract infection by P.mirabilis  when urine culture tested and, the concentration of IgG , IgM  antibody in balance also showing white blood cells in normal range .While rabbits females that inoculated by 145Ã—107">  cfu in positive control group showed urinary tract infection by P. mirabilis  after 7 days post inoculation the tested urine culture showed raised in IgG , IgM and white blood cells concentration. Conclusions In the present study, flagellin protein immunization in rabbit showed that there are rising in IgM and IgG titers. After challenging by ascending urinary tract infection, we showed neutralization of IgG and IgM and white blood cells.Keywords: Flagellin, P. Mirabilis, UTI, Vaccine.